Production of Inulin-Supplemented Dadih Using the Crude Leaf Extract of Kesinai (Streblus Asper) - Ishak, Ruzaina (2006)
The effects of extraction buffer pH, temperature,calcium chloride and enzyme concentration on milk coagulating activities of kesinai crude leaf extract were evaluated. The color of crude extract increased up to 47.90% by the increasing extraction buffer pH from 6.0 to 7.4. The protease and milk-coagulating activity of the crude extract was optimum at extraction buffer pH 7.2. Milk-coagulating activity was optimum at 70ºC. The addition of calcium chloride in the range 1 to 10 mM concentration into fresh milk has increased milk- coagulating activity by 12.42 to 20.15%,respectively. Milk coagulating activity also increased from 1.74 to 37.97% by the increasing of enzyme concentration in the range 10 to 100% v/v, respectively. The effect of sodium metabisulphite on color, protease and milk coagulating activity of kesinai crude leaf extract were also investigated. The required concentration of sodium metabisulphite for browning inhibition ranged from 0.5 to 10.0 mM,which decreased color by 61.90 to 87.60 % and increased protease activity by 11.26 to 14.15%, respectively. Milk coagulating activity increased from 11.29 to 18.03% for the similar concentration. The minimum threshold for inhibition of browning was 1mM,with the treated extract, having a higher protease and milk coagulating activity as compared to the control.‘Dadih’ was made from skim milk and fresh milk fortified with 5% to 9% of inulin and coagulated with kesinai leaf extract. Inulin increased the hardness, fracturability,cohesiveness and decreased syneresis of ‘dadih’.Sensory attributes tested for both types of ‘dadih’ were creaminess, sweetness, bitterness,firmness and total acceptance.The best product judged by the trained panelists was ‘dadih’ made from fresh milk with 9% of inulin. The findings indicate that inulin can be used as an additive in ‘dadih’ in order to improve the physical and sensory properties of ‘dadih’